The autoactivation of factor XII (Hageman factor) induced by low-Mr heparin and dextran sulphate. The effect of the Mr of the activating polyanion. - Silverberg, M (1987)
Human Factor XII is known to undergo autoactivation in the presence of dextran sulphate of Mr 500,000. We have now studied the dependence of this reaction on the Mr of the dextran sulphate by using fractions resolved by gel filtration. We have found that autoactivation can be induced by dextran sulphate fractions with Mr as low as 3000, and there is a marked dependence of the rate constant of autoactivation on the Mr value. Fractions with Mr below 8000 gave very low rates of autoactivation; there was a sharp increase in the rate obtained when the Mr of the dextran sulphate was greater than 10,000. Various preparations of heparin were also able to support the autoactivation of Factor XII and gave a very similar relationship between molecular size and reaction rate. The data provide support for the hypothesis that the mechanism by which the 'surface' acts in contact activation involves the presence, on the same particle, of multiple binding sites for the proteins.